The Contribution of the European Cohesion Policy to the 2030 Agenda: an Application to the Autonomous Region of Sardinia - Laura Cavalli; Sandro Sanna; Mia Alibegovic; Filippo Arras; Gianluca Cocco; Luca Farnia; Emanuela Manca; Luisa F. Mulas; Marco Onnis; Sandro Ortu; Ilenia G. Romani; Marta Testa (Fondazione Eni Enrico Mattei (FEEM), 2020)
The 2030 Agenda has been adopted on a global level, but its implementation must also take place at the local level (Cavalli, 2018). The integration between the different levels of government - supranational, national and local - is essential; they must necessarily cooperate and coordinate their actions to ensure the effective implementation of every Goal of the Agenda. It is evident that the European Union, with its Member States, is fully committed towards the implementation of the 2030 Agenda and its SDGs (Sanna et al., 2019). In particular, the concept of sustainable development, clearly stated in the five Strategic Objectives, is also expressed in future operational programmes in the context of Cohesion Policy. The latter is one of the most transversal policies of the European Union, including not only economic cohesion but also the social and territorial ones, and “contributes to most, if not all 17 SDGs" (European Commission, 2019). This paper proposes a methodology that evaluates the sustainability of the operational programmes co-financed by the Union with reference to the 169 targets of the 2030 Agenda and it is based specifically on the 143 intervention fields. The developed methodology can be used as a decision support tool for the European Union itself as a means of monitoring expenditure with reference to the 2030 Agenda in the various European Cohesion Policies. The present work briefly presents the model developed and its first results, deriving from the pilot applications to the Sardinia ERDF and ESF 2014-2020 ROPs.
Keywords: R58; H83; C43; Q56; 330; Sustainable Development; SDGs; Cohesion Policy; Localization